Comprehensive Characterization and Nonlinear Optical Properties of L-Histidine Diglycine Picrate (LHSDGP) Single Crystals for Advanced Photonic Applications - Suganthi, R.; Balasubramanian, K. (Journal of Scientific Research, 2026)
The L-Histidine Diglycine Picrate (LHSDGP) single crystal was carefully synthesized at room temperature using the slow evaporation solution technique (SEST), which allows for the gradual formation of LHSDGP crystals from a supersaturated solution under controlled conditions. The crystal's structure was confirmed through Single Crystal X-ray Diffraction, revealing an orthorhombic lattice within the P2₁2₁2₁ space group. To further validate its structural consistency, Powder X-ray Diffraction studies were also conducted. Fourier Transform Infrared (FTIR) spectroscopy was used for vibrational analysis, aiding in the identification of molecular groups and providing insight into the crystal's chemical composition. The mechanical properties of the crystal were assessed using microhardness testing, demonstrating its durability. Optical properties, including light absorption and transmission characteristics, were examined through UV-vis-NIR spectroscopy. The LHSDGP crystal's electrical response was analyzed through dielectric measurements, tracking changes in the dielectric constant and loss factor at three different temperatures. The TG/DTA analysis was conducted to determine the decomposition temperature and thermal endurance of the LHSDGP crystal. Notably, the laser damage threshold (LDT) of LHSDGP was found to be 2.7 GW/cm², highlighting its potential for high-power laser applications. Z-scan techniques evaluated the LHSDGP crystal's third-order nonlinear optical properties.